On the Accuracy of Density Functional Theory in Zeolite Catalysis. Issue 17 (23rd July 2019) - Goncalves, Tiago J.; Plessow, Philipp N.; Studt, Felix
Abstract: Zeolites are porous materials that are typically studied using periodic density functional theory (DFT). In this work we benchmark commonly used density functionals using cluster models for Brønsted acidic as well as copper substituted SSZ‐13 (H‐SSZ‐13 and Cu‐SSZ‐13). We find that for acid‐catalyzed reactions with relevance for the methanol‐to‐olefins process, barriers are the main challenge as they are commonly underestimated by DFT. For reactions involving Cu‐SSZ‐13 (commonly used for the selective catalytic reduction of NOx, SCR), reaction energies are already a challenge for most density functionals. Our results show that the widely used PBE‐D3 functional leads to mean absolute errors larger than 40 kJ/mol for barrier heights. Hybrid functionals show significant improvements with the best tested functional herein M06 having an error of only 7 kJ/mol. Abstract : Top tier ! The accuracy of DFT for reaction energies and transition states is investigated for MTO processes and the SCR mechanism, using different cluster models of Chabazite zeolite frameworks H‐SSZ‐13 and Cu‐SSZ‐13.